2016
DOI: 10.11152/mu-75
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of side dominance and ultrasonographic measurements of pronator quadratus muscle along with handgrip and pinch strength.

Abstract: Aims: We ascertained effects of hand dominance in both right and left-handed volunteers on the thickness and cross sectional area (CSA) of pronator quadratus (PQ) muscle as measured by the axial and sagittal views of ultrasound imaging. Secondly, we also aimed to document the extent of the relationship between the PQ measurements and handgrip. Materials and methods: Healthy adults from the volunteer medical staff were included in the study. Handedness was assessed via The Flinders Handedness survey. The sonogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In addition, Nusret et al reported a high intraobserver reliability on ultra sound examination in healthy individuals. 19 We could not reproduce similar high reliability but we found an overall moderate to good intraobserver reliability. This lower reliability could be caused by more difficult visualization of the PQ muscle due to the scar tissue after surgery.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, Nusret et al reported a high intraobserver reliability on ultra sound examination in healthy individuals. 19 We could not reproduce similar high reliability but we found an overall moderate to good intraobserver reliability. This lower reliability could be caused by more difficult visualization of the PQ muscle due to the scar tissue after surgery.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have demonstrated a difference in cross-sectional area (CSA) and thickness of the PQ muscle when comparing hand dominance. 17,19 However, we have not found studies that describe differences in the length of the PQ muscle when regarding hand dominance or left/right wrists. In our study, there was no significant difference in the lengths of the muscles in the uninjured wrist regardless of side or dominance.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[4][5][6][7] Ultrasonographic measurements of pronator quadratus muscle cross sectional area and muscle thickness have been shown to correlate with handgrip strength. 8 It would therefore be expected that the normalization of SWV values compared to the uninjured contralateral ''internal control'' wrist may allow an additional metric to evaluate and monitor the efficacy of physical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the patient and control groups, the dominant handwas included in the study of the LHBT. There are studies in the literature that show differences between dominant hand muscle strength and size [14][15][16]. Therefore, we preferred the LHBT on the side of the dominant hand.…”
Section: Study Population and Inclusion Criteriamentioning
confidence: 99%